Corporate governance in Kenya's state corporations: A critique on the appointment and dismissal of directors of boards of state corporations - Kamau, A. G. N. (University of Nairobi, 2013)
This study interrogates corporate governance practices within Kenya’s State Corporations with particular reference to the appointment and dismissal of directors of the Boards of these corporations. It recognizes that these directors are the anchors for the implementation of corporate governance practices in these corporations. The appointment and dismissal of these directors have been based on, inter alia, political considerations kinship, patronage, ethnicity and other non objective criteria other than merit. This has often impacted negatively on the performance of these corporations. This study traces the evolution of corporate governance generally, documents it’s historical development in Kenya and examines the current practices on the appointment and dismissal of directors of boards of state corporations. The data collected targeted a majority of State Corporations which demonstrates that past criteria for Directors recruitment and their dismissal was based on non objective criteria. The study is instructive on the fact that though best practice and corporate governance principles have not been fully embraced in the appointment and dismissal of Directors of Boards of State Corporations there is a positive move towards the adoption of these principles in such appointments and dismissals. The impetus for this was the promulgation of the Kenya constitution 2010 which is itself a good corporate governance document.

Da admissibilidade do direito de retenção no contrato de empreitada de construção imobiliária - Correia, Armando Francisco Gonçalves (Universidade Católica Portuguesa, 2013)
Keywords: Construction immobilière; Contrat; Droit de rétention; Immeuble (construction)

Business income and passive income in the UN model double taxation convention - Mascia, Susanna (LUISS Guido Carli, 2013)
The historical evolution of the UN model convention. The UN model convention’s subjective and objective scope. The determination of active income: current points of difference between the UN and OECD models. The determination of passive income: differences and similarities between the UN and the OECD model conventions. Transfer pricing.

"Arbitrato e Fallimento" - Anzilotti, Ilaria (Università di Pisa, 2013)
Grazie alla novella del 2006 è stato riformulato anche l’art. 25 n. 7 in relazione al potere di nomina degli arbitri attribuito al giudice delegato su proposta del curatore, l’art. Opposizioni allo stato passivo La riforma del 2006 ha profondamente inciso sulle impugnazioni allo stato passivo. La soluzione è stata poi abbandonata in virtù del mancato rispetto del principio del contraddittorio. Prima della riforma del 2006 era previsto solo il reclamo contro gli atti del curatore. Alla luce della riforma del 2006 questa tesi è però da respingere. La prima ipotesi concerne l’opponibilità alla procedura del lodo emesso in data anteriore alla sentenza dichiarativa di fallimento.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrato; Fallimento

Unlocking Africa's poverty trap : holistic approach to BOP investment in agribusiness - Suzuki, Elli (Massachusetts Institute of Technology, 2013)
This paper identifies subsistence farming as a significant opportunity for poverty reduction and economic development in sub-Saharan Africa. By taking a holistic, standardized, and bundled approach, this paper proposes an innovative business model that enables small-holder farmers to access affordable extension services, technical assistance and financial scheme, thereby improving their overall productivity level.

La formation des marins pour la sécurité maritime - Butaeye, Etienne (Aix-Marseille Université, 2013)

Les clauses de hardship dans les contrats maritimes - Carneiro, Laure (Aix-Marseille Université, 2013)

Les convois exceptionnels ITER - Drai, Laura (Aix-Marseille Université, 2013)

Lettre de garantie au déchargement : La pratique de la livraison sans connaissement - Palliatif autonome ou Substitut ? - Faali, Réza (Aix-Marseille Université, 2013)

Le beneficial owner et la saisie d'un navire autre que celui auquel la créance se rapporte - Farnier, Marion (Aix-Marseille Université, 2013)

Enjeux et difficultés de la navigation en Arctique et du développement des nouvelles voies maritimes : Le passage du Nord-Ouest et la route maritime du Nord - Graffin, Benoit (Aix-Marseille Université, 2013)

Le retard à la livraison dans le contrat de transport de marchandises par mer - Gwizdowski, Alexandra (Université Paul Cézanne Aix-Marseille 3, 2013)

A Comparative study of some issues relating to Corporate Insolvency Law in Nigeria and South Africa - Habi, Halita Mafo (University of Pretoria, 2013)
No abstract available

La gestion portuaire à Djibouti - Hassan Hoche, Guedi (Aix-Marseille Université, 2013)

La réforme du droit des transports maritimes en Allemagne - Le Feuvre, Nolwenn (Aix-Marseille Université, 2013)

L'ordonnance du 2 novembre 2012 portant réforme pénale en matière maritime - Martin, Karine (Aix-Marseille Université, 2013)

L'application des clauses du connaissement en Thaïlande - Sriphongkul, Nattika (Aix-Marseille Université, 2013)